2018
DOI: 10.18203/2320-1770.ijrcog20180519
|View full text |Cite
|
Sign up to set email alerts
|

Study of indications and post-operative complications of primary caesarean section in tertiary care hospital in Nepal

Abstract: Background: Caesarean section performed for appropriate obstetric or medical indications are life saving for both mother and new born. But its advantage does not justify its continuous increase as it is a major surgical procedure associated with maternal and fetal complications. The main objective of this study was to study the indications of primary caesarean section and its maternal and fetal complications in Nepal medical college teaching hospital (NMCTH).Methods: This is a hospital based cross sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In a study done by Datta et al, it showed that the maximum number of cases (79.34%) had an age between 20-30 years which is very similar to the study done by Jain et al, Mande et al, by Rajbhandary et al, by Rao et al, Boyle et al as well as our study where the maximum age distribution was seen among 18-27 years of age (62.3%). 5,8,9,[11][12][13] This shows that most of the primigravida who underwent caesarean section were in the age group of 20-30 years in most studies. Our study had 16 elderly primigravida accounting to 4.2% of the study population.…”
Section: Discussionmentioning
confidence: 84%
“…In a study done by Datta et al, it showed that the maximum number of cases (79.34%) had an age between 20-30 years which is very similar to the study done by Jain et al, Mande et al, by Rajbhandary et al, by Rao et al, Boyle et al as well as our study where the maximum age distribution was seen among 18-27 years of age (62.3%). 5,8,9,[11][12][13] This shows that most of the primigravida who underwent caesarean section were in the age group of 20-30 years in most studies. Our study had 16 elderly primigravida accounting to 4.2% of the study population.…”
Section: Discussionmentioning
confidence: 84%
“…Literature supports the routine induction of labour at 41 weeks in uncomplicated pregnancies [23] . The most common indication for primary caesarean in Rajbhandary [19] S et al was foetal distress (40%) followed by cephalopelvic disproportion (15%), breech presentation (10%) and non-progress of labour (9%). Primary caesarean delivery in Cheluvamba hospital, Mysore Medical College Research Institute accounted for 40.3% cases of foetal distress, failed induction (13.6%), breech (10%), CPD (8%), IUGR with poor BPP (1.8%) and antepartum haemorrhage (3%) and deep transverse arrest (3.5%) [9] , while Samal R et al [24] , study shows foetal distress (42.6%) malpresentation (26.4%) CPD (14.7%) and cord prolapse (1.5%).The two most common indications of primary caesarean in Nigar et al were arrest of labour (18.1%) and CPD (14.2%) followed by foetal distress(12.9%), malpresentation (5.2%), and failed induction (4.8%).…”
Section: Indications Of Primary Caesarean Deliverymentioning
confidence: 99%
“…The rural-urban gap is relatively low in the states of Kerala [17] , Haryana, Delhi, Arunachal Pradesh (below 5 percentage points) as evidenced in the research here while the gap is very high in the states of Jammu and Kashmir, West Bengal and Tripura (above 20 percentage points) [18] . Moreover, the demographic and socioeconomic backgrounds of the persons living in the rural and urban places affect the CS rate to a great extent [19] . Income had positive association with pattern of previous caesarean delivery in contrast to Balmur SK [20] et al 8.7% primary caesareans were obstetric referrals with one or more associated morbidities which added to the burden of caesarean delivery.…”
Section: Socio-demographic and Caesarean Deliverymentioning
confidence: 99%
“…PPH, urological complications, infections and pulmonary embolism are major immediate complications. Severe maternal morbidities like hemorrhage, uterine rupture, anesthetic complications, shock, cardiac arrest, acute renal failure, assisted ventilation, venous thromboembolism, major infection, or in-hospital wound disruption or hematoma were increased threefold for cesarean delivery as compared with vaginal delivery: 2.7% and 0.9%, respectively [19][20][21]. Serious consequences in subsequent pregnancies include spontaneous preterm birth, uterine rupture, placenta previa and accreta and occasionally obstetric hysterectomy.…”
Section: Sequele and Risk Of Repeat C-sectionmentioning
confidence: 99%